2019
DOI: 10.1002/pds.4860
|View full text |Cite
|
Sign up to set email alerts
|

National trends in hydroxyurea and opioid prescribing for sickle cell disease by office‐based physicians in the United States, 1997‐2017

Abstract: Purpose To identify trends in physician drug prescribing practices for sickle cell disease (SCD). Methods We used data from the National Disease and Therapeutic Index to evaluate medications prescribed to children (definition: aged 19 years or younger) and adults (20 years or older) with SCD by office‐based physicians in the United States during 1997 to 2017. Prescriptions were evaluated in 3‐year intervals. Results The proportion of SCD visits that included new/continued hydroxyurea prescriptions increased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 13 publications
4
34
1
Order By: Relevance
“…19 While the 2014 guidelines increased the early initiation of hydroxyurea, use remains concerningly low with recent data suggesting that less than 50% of children with SCA are prescribed this life-saving medication. 20,21 In addition to the importance of early initiation of hydroxyurea to prevent SCA complications, our experience documents that hydroxyurea dosing is also a critically important determinant to optimize the clinical and laboratory effects of the medication. The clinical bene ts of hydroxyurea are maximized when the HbF production is optimized and HbF effect is largely determined by degree of hydroxyurea exposure.…”
Section: Introductionmentioning
confidence: 99%
“…19 While the 2014 guidelines increased the early initiation of hydroxyurea, use remains concerningly low with recent data suggesting that less than 50% of children with SCA are prescribed this life-saving medication. 20,21 In addition to the importance of early initiation of hydroxyurea to prevent SCA complications, our experience documents that hydroxyurea dosing is also a critically important determinant to optimize the clinical and laboratory effects of the medication. The clinical bene ts of hydroxyurea are maximized when the HbF production is optimized and HbF effect is largely determined by degree of hydroxyurea exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of specialists, adult SCD patients visit the ED more often and visit hematology/oncology specialists less often than do children. 52 When an SCD pain crisis does occur, it should be treated appropriately and adequately. As found in the CDC's clarification letter responding to concerns issued by the American Society of Clinical Oncology, the American Society of Hematology, and the National Comprehensive Cancer Network, special consideration should be given to SCD patients' pain management, and access to appropriate pain management should not be limited.…”
Section: Discussionmentioning
confidence: 99%
“…33 , 49 , 50 Hydroxyurea has shown its beneficial effects in reducing the number of VOC events for the last two decades. 19 , 24 , 25 , 51 However, hydroxyurea prescribing is infrequent and even more infrequent than opioid prescribing among adults with SCD, 52 which could be due to physicians’ concerns about blood-monitoring requirements and patients’ general nonadherence with the therapy. 53 , 54 L-glutamine oral powder, approved by the US Food and Drug Administration in July 2017, can be added to hydroxyurea to further reduce VOC events.…”
Section: Discussionmentioning
confidence: 99%
“…The BABY HUG trial, which demonstrated safety and efficacy of starting HU in infancy contributed to a robust increase in HU prescribing for children with SCD. 62 Hydroxyurea use in infants 5-12 months old resulted in a better response compared with use in older patients. 63 Moreover, prospective longitudinal follow-up of children with SCD treated with HU since infancy was highly effective in preventing complications of SCD.…”
Section: Amentioning
confidence: 99%